พฤติกรรมการท่องเที่ยวเชิงพุทธศาสนาของนักท่องเที่ยว วัด ในจังหวัดน่าน - ธนิต บุตรทิพย์สกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The objective of this research is to study the behaviors of Thai tourists visiting the temples in Nan Province for religion tourism. The research is based on demographic information, the conceptual framework of religion tourism, behaviors of Thai tourists and the five components of religion tourism: architecture and painting, Dharma discussion or meditation, purchasing of amulets, merit-making to removal of bad luck through ceremony and participation in activities organized by the temples. This research was conducted by taking purposive sampling from random tourists of Thai nationality, whereby 400 people were asked to take a questionnaire. The questionnaire’s Index of Item Objective Congruence value (IOC) is equal to 0.93. The reliability of the questionnaire calculated by Cronbach’s Alpha Coefficient is 0.83. Analysis from the data collected from the questionnaires by using frequency distribution, percentage and Chi-Square Statistic to estimate and find the relation between the variables which show a significant 0.05 level. The study on demographic information of Thai tourists shows that 58.1 percent were female and 41.9 percent were male. Most of the respondents were between the ages of 21-40 years old, single, having bachelor’s degree, working as employees in private companies, whose average income ranged between THB 5,000 to THB 30,000 per month, having their domicile in the central region of Thailand, having uncertain frequency of traveling, travelling by private vehicles during holidays of more than 3 days with friends/lovers and mostly staying at the hotels. Choices of travelling were based on the information obtained through the media/magazines/online media or social media. They were attracted to Nan province by its famous tourist attractions i.e. the beautiful landscape, various tourist attractions and local cultures with most of the travelling period is 3-4 days. Moreover, it was found that most questionnaire respondents had travelled to Nan Province for the first time for its architecture and painting. The reason for travelling to the temples was to worship or pray according to their faith and to buy amulets in the belief of becoming wealthy. They spent about half an hour on sightseeing at the temple, which cost between THB 51 to THB 100. They preferred travelling during the yearly temple fair with impressive and relaxed feelings. The relation between the variables calculated by using Chi Square Statistic shows that demographic information of the tourists, which are gender, age, education, occupation, income per month and domicile, have statistically significant relation with the five components of religion tourism (P <0.05), except for the gender of the tourists, which is not related to merit-making to removal of bad luck through ceremony (P> 0.05, sig = .391), and marital status (single, married, widowed/divorced) of tourists is not related to Dharma discussion or meditation (P> 0.05, sig = .196), which should be studied in comparison with the behaviors of tourists who travel to other provinces or regions in Thailand for religious purposes in the future.